Simulation and Experimental Study on Transmission Precision of RV Reducer based on Rigid-flexible Coupling - Lu Qi; He Weidong; Wu Xinhui (Jixie chuandong)
The rigid-flexible couple virtual prototype model of RV reducer which including machining errors,assembly errors,elastic deformation and clearance is established. The dimension and error variables of the virtual prototype model are parameterized. In order to determine the main factors,the transmission error curve of RV reducer under the action of different error factors is obtained. According to the main error factors,the orthogonal test is used to analyze the transmission precision of the RV reducer. The transmission accuracy of RV reducer is tested by grating method. The simulation model is modified and verified by comparing the simulation results with the experimental results.